Preparation method and application of bifunctional Schottky heterojunction type electrolyzed water catalyst
By forming a Schottky heterojunction structure with titanium dioxide and transition metal doped ruthenium oxide, the problem of high cost of precious metal catalysts in electrolytic hydrogen production reaction is solved, and an efficient and inexpensive dual-function catalyst is achieved, with performance surpassing commercial catalysts , and reduces reaction energy consumption.
Patent Information
- Application Number
- CN202311677615.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-06
- Publication Date
- 2024-12-13
AI Technical Summary
In the prior art, electrolytic water hydrogen production reaction requires high precious metal catalysts, which limits their inexpensive and efficient use in large-scale applications. In particular, the research of bifunctional catalysts is particularly important.
The sol-gel method uses the sol-gel method to form a Schottky heterojunction structure, and uses a built-in electric field to optimize the charge distribution, realizing the preparation of a dual-function catalyst, which can be applied to the anode and cathode catalysts that can be used simultaneously in electrolyzed water. , reduces the over-potential and energy consumption.
The dual-function catalyst prepared by this method has excellent performance, surpassing commercial Pt/C and commercial RuO2 catalysts, reducing the amount and production cost of noble metal ruthenium, improving the efficiency of electrolytic water reaction, and achieving a dual-function catalytic effect.
Smart Images

Figure CN119121311A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electrochemical catalysis, and in particular to a preparation method of a bifunctional Schottky heterojunction water electrolysis catalyst and application thereof. Background Art
[0002] Hydrogen energy is recognized as a clean energy source with high combustion calorific value and the product is water. It is a truly clean energy source. As an important secondary energy source, hydrogen energy is expected to become the most watched energy source on the world energy stage in the 21st century. The development of hydrogen energy is conducive to reducing dependence on oil, ensuring energy security, reducing air pollution and greenhouse gas emissions, helping the transformation and upgrading of the automobile industry, enhancing independent innovation capabilities, and developing new economic growth points. The hydrogen production reaction by electrolysis of water includes two half reactions: the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). Among them, OER is also a key step in the technical reaction of devices such as fuel cells and metal-air batteries. This type of reaction process is complex and has a high energy barrier. It usually requires a large overpotential drive. Its kinetic performance restricts the overall performance of the device, so a highly active electrocatalyst is required.
[0003] The hydrogen evolution reaction currently mainly uses Pt-based precious metal catalysts, while the oxygen evolution reaction mainly uses IrO 2 and RuO 2 However, the limited reserves and high prices of precious metal catalysts restrict their large-scale application in water electrolysis. Therefore, the preparation of cheap and efficient water electrolysis catalysts is an important scientific problem to be solved, especially the research on bifunctional catalysts. Summary of the invention
[0004] The technical problem to be solved by the present invention is: how to prepare a cheap and efficient bifunctional water electrolysis catalyst. The present invention uses a sol-gel method to compound titanium dioxide and transition metal-doped ruthenium oxide to form a catalyst with a unique Schottky heterojunction structure. A trace amount of transition metal salt can be well adsorbed on the surface or near the ruthenium salt, creating a prerequisite for uniformly dispersed doped ruthenium oxide; the built-in electric field formed by the Schottky heterojunction promotes spontaneous charge transfer and optimizes the charge distribution. As a bifunctional catalyst, it can be used as an anode catalyst and a cathode catalyst for hydrogen production by electrolysis of water, and has excellent catalytic performance, surpassing commercial Pt / C and commercial RuO 2 When used in water electrolysis to produce hydrogen, it greatly reduces the overpotential of the hydrogen evolution reaction and the overpotential of the oxygen evolution reaction, reduces the reaction energy consumption, improves the efficiency of the water electrolysis reaction, and also reduces the amount of precious metal ruthenium used, thereby reducing production costs.
[0005] To achieve the above-mentioned purpose, the present invention provides the following technical solution: a bifunctional Schottky heterojunction type water electrolysis catalyst, comprising titanium dioxide nanoparticles and transition metal-doped ruthenium oxide nanoparticles, and the two are connected by a Schottky heterojunction; the content of ruthenium oxide in the catalyst is 1% to 20%, and the content of transition metal is 0.2% to 4%.
[0006] The above-mentioned method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst comprises the following steps:
[0007] S1: Preparation of titanium dioxide gel according to the sol-gel method;
[0008] S2: adding ruthenium salt and transition metal salt to the obtained gel to obtain a precursor material;
[0009] S3: Sintering the precursor material to obtain a bifunctional Schottky heterojunction water electrolysis catalyst.
[0010] Preferably, the step 1 specifically comprises: weighing butyl titanate and adding it to ethanol, then adding glacial acetic acid and mixing to obtain a mixed solution, dropping the ethanol-water solution into the mixed solution, continuously stirring and drying to obtain titanium dioxide gel;
[0011] The porous nature of the gel is conducive to the adsorption and dispersion of metal salts.
[0012] Preferably, the volume ratio of butyl titanate to ethanol is 0.5-1:1, the volume ratio of butyl titanate to glacial acetic acid is 1-3:1, and the volume ratio of deionized water to ethanol in the ethanol-water solution is 0.5-1:2.
[0013] Preferably, after obtaining the mixed solution, the pH value needs to be adjusted to 1-3, and the inorganic acid used for adjustment is one or more of hydrochloric acid, nitric acid, and sulfuric acid, and the concentration of the inorganic acid is 2-5M; the continuous stirring time is 8-24h, and the drying temperature is 40-80°C.
[0014] Preferably, the step 2 is specifically as follows: dispersing the obtained gel in a solvent, dropping 1 to 5 mg / mL of a ruthenium salt solution, soaking for reaction, filtering, and drying to obtain a product; dispersing the obtained product in a solvent again, dropping 0.1 to 0.5 mg / mL of a transition metal salt solution, soaking for reaction, filtering, and drying to obtain a precursor material;
[0015] Since the gel has abundant pores and oxygen-containing functional groups, it can evenly and dispersely load ruthenium salts to reduce the agglomeration of metal nanoparticles. The addition of transition metal salts lays the foundation for the formation of doped ruthenium oxide. The transition metal is doped into the lattice of ruthenium oxide, which can spontaneously induce the transfer of charge between the transition metal and ruthenium metal, thereby optimizing the overall charge distribution of the catalytic material and improving the intrinsic catalytic activity of the active sites.
[0016] Preferably, the concentration of the gel in the solvent is 10 to 50 mg / mL, the mass ratio of the gel to the ruthenium salt is 1:0.01 to 0.2, the concentration of the product in the solvent is 10 to 50 mg / mL, the mass ratio of the ruthenium salt to the transition metal salt is 1:0.1 to 0.3, the temperature of the immersion reaction is 25 to 60°C, and the time is 12 to 24 hours.
[0017] Preferably, the ruthenium salt is one or more of hydrated ruthenium chloride, bis(pentamethylcyclopentene)ruthenium, bis(cyclooctadiene)ruthenium chloride, (1,5-cyclooctadiene)ruthenium chloride, the transition metal salt is one or more of cupric chloride hexahydrate, nickel chloride hexahydrate, cobalt chloride hexahydrate, and manganese chloride tetrahydrate, and the solvent is one or more of deionized water, methanol, ethanol, isopropanol, and ethylene glycol.
[0018] Preferably, the sintering treatment is carried out at a temperature of 250-600° C., for a time of 2-8 h, at a heating rate of 3-5° C. / min, and in an air atmosphere.
[0019] After calcination, the gel will form very uniform and fine titanium dioxide nanoparticles, while the ruthenium salt and transition metal salt will be oxidized to form doped ruthenium oxide, and very evenly compounded with titanium dioxide. The metallic doped ruthenium oxide and the n-type semiconductor titanium dioxide form a Schottky heterojunction structure. This interface structure effect will form a built-in electric field, spontaneously promoting the spontaneous transfer of charge from titanium dioxide to ruthenium oxide, optimizing the charge distribution, and improving the intrinsic catalytic activity of the material.
[0020] Application of any of the above-mentioned bifunctional Schottky heterojunction water electrolysis catalysts as anode or cathode material in hydrogen production by water electrolysis.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] (1) The catalyst prepared by the present invention forms a unique Schottky heterostructure, in which transition metal-doped ruthenium oxide and n-type semiconductor titanium dioxide form a heterojunction interface. The difference in work function promotes the formation of a built-in electric field, allowing charges to flow spontaneously from titanium dioxide to ruthenium oxide, thereby optimizing the charge distribution of the material and improving the intrinsic catalytic activity.
[0023] (2) The catalyst prepared by the present invention is a bifunctional catalyst, which can be used as both an anode oxygen evolution reaction catalyst and a cathode hydrogen evolution reaction catalyst in water electrolysis, achieving a bifunctional effect of the catalyst, and its performance exceeds that of commercial RuO 2 Catalysts and commercial Pt / C catalysts greatly reduce the use of precious metals and reduce costs.
[0024] (3) The electrocatalyst preparation method of the present invention is simple and low-cost. Large-scale and macro-quantitative catalyst preparation can be achieved through simple stirring and impregnation reaction at room temperature and pressure and low-temperature calcination in air atmosphere. The preparation process is green and environmentally friendly, and no wastewater or waste gas is discharged. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 TiO 2 @Cu-RuO 2 、TiO 2 @RuO 2 With commercial RuO 2 OER reaction linear voltammetry (OER-LSV) of the catalyst;
[0026] Figure 2 TiO 2 @Cu-RuO 2 、TiO 2 @RuO 2 HER reaction linear voltammetry curve (HER-LSV) with commercial Pt / C catalyst;
[0027] Figure 3 TiO 2 @Cu-RuO 2 Linear voltammetry (LSV) curve of water electrolysis reaction as a bifunctional catalyst;
[0028] Figure 4 TiO 2 @Cu-RuO 2 Transmission electron microscope image of the catalyst;
[0029] Figure 5 TiO 2 @Cu-RuO 2 Schottky heterojunction structure interface of the catalyst. DETAILED DESCRIPTION
[0030] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0031] Embodiment 1:
[0032] Preparation of bifunctional Schottky heterojunction titanium dioxide composite copper-doped ruthenium oxide water electrolysis catalyst;
[0033] (1) Deionized water (5 mL) was added to ethanol (20 mL), and after stirring at room temperature for 30 minutes, a hydrochloric acid (2 M) aqueous solution was slowly added dropwise to adjust the pH value to 1 to obtain solution A; butyl titanate (10 mL) was added to ethanol (20 mL), and after stirring at room temperature for 30 minutes, glacial acetic acid (10 mL) was slowly added dropwise to obtain solution B; solution A was slowly added dropwise to solution B under stirring, and after stirring for 8 hours, the mixture was placed in an oven at 40° C. for drying to obtain titanium dioxide gel;
[0034] (2) The obtained gel material (5.0 g) was added to deionized water (500 mL), and then an aqueous solution of hydrated ruthenium chloride (1 mg / mL, 50 mL) was slowly added dropwise at a uniform rate, and then the mixture was soaked at 25° C. for 12 hours, and then filtered and dried at room temperature for 12 hours to obtain a product; The obtained product (5.0 g) was added to deionized water (500 mL), and then an aqueous solution of hexahydrated copper chloride (0.1 mg / mL, 50 mL) was slowly added dropwise at a uniform rate, and then the mixture was soaked at 25° C. for 12 hours, and then filtered and dried at room temperature for 12 hours to obtain a precursor material;
[0035] (3) Under air conditions, the precursor material was placed in a quartz boat, placed in a muffle furnace, heated to 250°C at a heating rate of 3°C / min, and calcined at 250°C for 2 hours. After calcination, it was naturally cooled to room temperature to obtain a bifunctional Schottky heterojunction titanium dioxide composite copper-doped ruthenium oxide electrolytic water catalyst (TiO 2 @Cu-RuO 2 ).
[0036] Embodiment 2:
[0037] Preparation of bifunctional Schottky heterojunction titanium dioxide composite nickel-doped ruthenium oxide water electrolysis catalyst;
[0038] (1) Deionized water (5 mL) was added to ethanol (16 mL), and after stirring at room temperature for 30 minutes, a nitric acid (3 M) aqueous solution was slowly added dropwise to adjust the pH value to 2 to obtain solution A; butyl titanate (10 mL) was added to ethanol (16 mL), and after stirring at room temperature for 30 minutes, glacial acetic acid (5 mL) was slowly added dropwise to obtain solution B; solution A was slowly added dropwise to solution B under stirring, and after stirring for 12 hours, the mixture was placed in an oven at 50° C. for drying to obtain titanium dioxide gel;
[0039] (2) The obtained gel material (5.0 g) was added to deionized water (250 mL), and then an aqueous solution of bis(pentamethylcyclopentene)ruthenium (2 mg / mL, 125 mL) was slowly added dropwise at a uniform rate, and then the mixture was soaked at 40° C. for 18 hours, and then filtered and dried at room temperature for 12 hours to obtain a product; The obtained product (5.0 g) was added to deionized water (250 mL), and then an aqueous solution of nickel chloride hexahydrate (0.2 mg / mL, 250 mL) was slowly added dropwise at a uniform rate, and then the mixture was soaked at 50° C. for 18 hours, and then filtered and dried at room temperature for 12 hours to obtain a precursor material;
[0040] (3) Under air conditions, the precursor material was placed in a quartz boat, placed in a muffle furnace, heated to 400°C at a heating rate of 4°C / min, and calcined at 400°C for 4 hours. After calcination, it was naturally cooled to room temperature to obtain a bifunctional Schottky heterojunction titanium dioxide composite nickel-doped ruthenium oxide electrolytic water catalyst (TiO 2 @Ni-RuO 2 ).
[0041] Embodiment 3:
[0042] Preparation of bifunctional Schottky heterojunction titanium dioxide composite cobalt-doped ruthenium oxide water electrolysis catalyst;
[0043] (1) Deionized water (5 mL) was added to ethanol (13 mL), and after stirring at room temperature for 30 minutes, a sulfuric acid (4 M) aqueous solution was slowly added dropwise to adjust the pH value to 3 to obtain solution A; butyl titanate (10 mL) was added to ethanol (13 mL), and after stirring at room temperature for 30 minutes, glacial acetic acid (3 mL) was slowly added dropwise to obtain solution B; solution A was slowly added dropwise to solution B under stirring, and after stirring for 24 hours, the mixture was placed in an oven at 60° C. for drying to obtain titanium dioxide gel;
[0044] (2) The obtained gel material (5.0 g) was added to deionized water (170 mL), and then an aqueous solution of bis(cyclopentadienyl) ruthenate (3 mg / mL, 170 mL) was slowly added dropwise at a uniform rate, and then the mixture was immersed at 50° C. for 24 hours, and then the mixture was filtered and dried at room temperature for 12 hours to obtain a product; The obtained product (5.0 g) was added to deionized water (170 mL), and then an aqueous solution of cobalt chloride hexahydrate (0.3 mg / mL, 500 mL) was slowly added dropwise at a uniform rate, and then the mixture was immersed at 60° C. for 24 hours, and then the mixture was filtered and dried at room temperature for 12 hours to obtain a precursor material;
[0045] (3) Under air conditions, the precursor material was placed in a quartz boat, placed in a muffle furnace, heated to 250°C at a heating rate of 5°C / min, and calcined at 500°C for 6 hours. After calcination, it was naturally cooled to room temperature to obtain a bifunctional Schottky heterojunction titanium dioxide composite cobalt-doped ruthenium oxide electrolytic water catalyst (TiO 2 @Co-RuO 2 ).
[0046] Embodiment 4:
[0047] Preparation of bifunctional Schottky heterojunction titanium dioxide composite manganese-doped ruthenium oxide water electrolysis catalyst;
[0048] (1) Deionized water (5 mL) was added to ethanol (10 mL), and after stirring at room temperature for 30 minutes, a nitric acid (5 M) aqueous solution was slowly added dropwise to adjust the pH value to 3 to obtain solution A; butyl titanate (10 mL) was added to ethanol (10 mL), and after stirring at room temperature for 30 minutes, glacial acetic acid (3 mL) was slowly added dropwise to obtain solution B; solution A was slowly added dropwise to solution B under stirring, and after stirring for 24 hours, the mixture was placed in an oven at 80° C. for drying to obtain titanium dioxide gel;
[0049] (2) The obtained gel material (5.0 g) was added to deionized water (100 mL), and then an aqueous solution of (1,5-cyclooctadiene)ruthenium chloride (5 mg / mL, 200 mL) was slowly added dropwise at a uniform rate, and then the mixture was soaked at 60° C. for 24 hours, and then filtered and dried at room temperature for 12 hours to obtain a product; the obtained product (5.0 g) was added to deionized water (100 mL), and then an aqueous solution of manganese chloride tetrahydrate (0.5 mg / mL, 600 mL) was slowly added dropwise at a uniform rate, and then the mixture was soaked at 60° C. for 24 hours, and then filtered and dried at room temperature for 12 hours to obtain a precursor material;
[0050] (3) Under air conditions, the precursor material was placed in a quartz boat, placed in a muffle furnace, heated to 600°C at a heating rate of 5°C / min, and calcined at 600°C for 8 hours. After calcination, it was naturally cooled to room temperature to obtain a bifunctional Schottky heterojunction titanium dioxide composite manganese-doped ruthenium oxide electrolytic water catalyst (TiO 2 @Mn-RuO 2 ).
[0051] Comparative Example 1:
[0052] A bifunctional Schottky heterojunction titanium dioxide composite ruthenium oxide water electrolysis catalyst is prepared, which is different from Example 1 in that there is no transition metal doping;
[0053] (1) Deionized water (5 mL) was added to ethanol (20 mL), and after stirring at room temperature for 30 minutes, a hydrochloric acid (2 M) aqueous solution was slowly added dropwise to adjust the pH value to 1 to obtain solution A; butyl titanate (10 mL) was added to ethanol (20 mL), and after stirring at room temperature for 30 minutes, glacial acetic acid (10 mL) was slowly added dropwise to obtain solution B; solution A was slowly added dropwise to solution B under stirring, and after stirring for 8 hours, the mixture was placed in an oven at 40° C. for drying to obtain titanium dioxide gel;
[0054] (2) adding the obtained gel material (5.0 g) into deionized water (500 mL), then slowly adding an aqueous solution of hydrated ruthenium chloride (1 mg / mL, 50 mL) at a uniform rate, and then soaking at 25° C. for 12 hours, then filtering, and drying at room temperature for 12 hours to obtain a precursor material;
[0055] (3) Under air conditions, the precursor material was placed in a quartz boat, placed in a muffle furnace, heated to 250°C at a heating rate of 3°C / min, and calcined at 250°C for 2 hours. After calcination, it was naturally cooled to room temperature to obtain a bifunctional Schottky heterojunction titanium dioxide composite ruthenium oxide water electrolysis catalyst (TiO 2 @RuO 2 ).
[0056] Catalyst performance test:
[0057] 1.0 mg of the bifunctional Schottky heterojunction titanium dioxide composite copper-doped ruthenium oxide electrolytic water catalyst (TiO 2 @Cu-RuO 2 ), the bifunctional Schottky heterojunction titanium dioxide composite ruthenium oxide water electrolysis catalyst (TiO 2 @RuO 2 ), Commercial RuO 2The catalyst, commercial Pt / C and four other electrocatalysts were prepared. Each catalyst was then dispersed in 200 μL of ethanol and 9.8 μL of Nafion solution. After ultrasonic mixing, 20 μL of the slurry was applied to a rotating disk electrode. After it was completely dried, the TiO 2 @Cu-RuO 2 、TiO 2 @RuO 2 and commercial RuO 2 Oxygen evolution reaction linear voltammetry (OER-LSV) curve of the catalyst, determination of TiO 2 @Cu-RuO 2 、TiO 2 @RuO 2 The linear voltammetric curves of hydrogen evolution reaction (HER-LSV) of commercial Pt / C catalysts and TiO 2 @Cu-RuO 2 The linear voltammetry (LSV) curve of water electrolysis reaction as a bifunctional catalyst. The linear voltammetry (OER-LSV) curve of oxygen evolution reaction (OER-LSV) and the linear voltammetry (HER-LSV) curve of hydrogen evolution reaction (HER-LSV) were measured with a saturated Ag / AgCl electrode as the reference electrode, a Pt electrode as the counter electrode, a scan rate of 5 mV / s, and an electrolyte of 1 mol / L KOH solution. 2 @Cu-RuO 2 The linear voltammetric (LSV) curve of water electrolysis reaction with TiO as a bifunctional catalyst 2 @Cu-RuO 2 The two-electrode water electrolysis reaction test was carried out using the two electrodes as the working electrode and the counter electrode, respectively. The scan rate was 5 mV / s and the electrolyte was 1 mol / L KOH solution.
[0058] The oxygen evolution reaction linear voltammetry (OER-LSV) curve obtained by the test is as follows: Figure 1 As shown, it can be clearly seen that the catalyst TiO in 1M KOH solution 2 @Cu-RuO 2 At 10mA / cm 2 The overpotential is 270mV. Under the same conditions, commercial RuO 2 The overpotential of the catalyst is 300 mV, which is 30 mV lower, effectively reducing the overpotential of the oxygen evolution reaction, and the performance is significantly better than that of commercial RuO 2 catalyst; while the non-transition metal doped catalyst TiO 2 @RuO 2 At 10mA / cm 2 The overpotential is 290 mV, which is significantly worse than that of the copper-doped catalyst TiO 2 @Cu-RuO 2, the difference is more obvious at high current density, indicating that transition metal doping effectively optimizes the charge distribution of the material and improves the intrinsic catalytic activity of the active sites.
[0059] Figure 2 The linear voltammetric (HER-LSV) curve of hydrogen evolution reaction obtained for testing clearly shows that the catalyst TiO 2 @Cu-RuO 2 At 10mA / cm 2 The overpotential of the catalyst is 19 mV, while the overpotential of the commercial Pt / C catalyst under the same conditions is 29 mV, which is 10 mV lower, effectively reducing the overpotential of the hydrogen evolution reaction, and the performance is significantly better than that of the commercial Pt / C catalyst. 2 @RuO 2 At 10mA / cm 2 The overpotential is 47 mV, and the HER catalytic performance is significantly worse than that of the copper-doped catalyst TiO 2 @Cu-RuO 2 Similarly, the overpotential difference at high current density is more significant, which also shows that transition metal doping can induce spontaneous charge transfer between transition metal elements and ruthenium elements, thereby optimizing the charge distribution of the material and improving the catalytic performance.
[0060] Figure 3 For a two-electrode system with TiO 2 @Cu-RuO 2 The linear voltammetric curve of the electrolytic water splitting reaction in which the catalyst is used as both an anode oxygen evolution catalyst and a cathode hydrogen evolution catalyst shows that in 1M KOH solution, 10 mA / cm 2 The water splitting overpotential is only 230mV, which greatly reduces the overpotential of water electrolysis, reduces power loss, and improves the efficiency of water electrolysis reaction.
[0061] Catalyst morphology analysis:
[0062] Figure 4 Bifunctional Schottky heterojunction titanium dioxide composite copper-doped ruthenium oxide water electrolysis catalyst TiO 2 @Cu-RuO 2 From the transmission electron microscope image, we can see that the nanoparticles of the catalyst are very uniform and small. The titanium dioxide particle size is about 8-12nm, and the nanoparticle morphology is consistent. The copper-doped ruthenium oxide nanoparticles are even smaller, with a particle size of about 2nm. Such uniform and small catalyst nanoparticles are very conducive to the full exposure of active sites, which can fully contact and react with the electrolyte, thereby comprehensively improving the intrinsic activity of the catalyst.
[0063] Figure 5 Bifunctional Schottky heterojunction titanium dioxide composite copper-doped ruthenium oxide water electrolysis catalyst TiO 2 @Cu-RuO 2 The Schottky heterojunction structure interface image shows that the ruthenium oxide nanoparticles and the titanium dioxide nanoparticles form a very good heterojunction interface. The lattice interface is very clear. The difference between their work functions can form a built-in electric field, which spontaneously promotes the flow of charge from titanium dioxide to copper-doped ruthenium oxide, optimizes the charge distribution, and improves the catalytic activity, thereby making TiO 2 @Cu-RuO 2 It has dual catalytic effects of OER and HER and is a bifunctional catalyst with excellent performance.
[0064] It is obvious to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be regarded as exemplary and non-limiting from any point of view, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims are included in the present invention, and any reference numerals in the claims should not be regarded as limiting the claims involved.
Claims
1. A bifunctional Schottky heterojunction water electrolysis catalyst, It is characterized in that The catalyst comprises titanium dioxide nanoparticles and transition metal-doped ruthenium oxide nanoparticles, and the two are connected via a Schottky heterojunction; the content of ruthenium oxide in the catalyst is 1% to 20%, and the content of the transition metal is 0.2% to 4%.
2. A method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst according to claim 1, It is characterized in that The steps include: S1: Preparation of titanium dioxide gel according to the sol-gel method; S2: adding ruthenium salt and transition metal salt to the obtained gel to obtain a precursor material; S3: Sintering the precursor material to obtain a bifunctional Schottky heterojunction water electrolysis catalyst.
3. A method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst according to claim 2, It is characterized in that The step 1 specifically comprises: weighing butyl titanate and adding it into ethanol, then adding glacial acetic acid and mixing well to obtain a mixed solution, dropping the ethanol-water solution into the mixed solution, continuously stirring and drying to obtain titanium dioxide gel.
4. A method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst according to claim 3, It is characterized in that The volume ratio of butyl titanate to ethanol is 0.5-1:1, the volume ratio of butyl titanate to glacial acetic acid is 1-3:1, and the volume ratio of deionized water to ethanol in the ethanol-water solution is 0.5-1:
2.
5. A method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst according to claim 3, It is characterized in that After obtaining the mixed solution, the pH value needs to be adjusted to 1-3, and the inorganic acid used is adjusted to one or more of hydrochloric acid, nitric acid, and sulfuric acid, and the concentration of the inorganic acid is 2-5M; the continuous stirring time is 8-24h, and the drying temperature is 40-80°C.
6. A method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst according to claim 2, It is characterized in that The step 2 is specifically as follows: dispersing the obtained gel in a solvent, dropping 1 to 5 mg / mL of a ruthenium salt solution, soaking for reaction, filtering, and drying to obtain a product; dispersing the obtained product in a solvent again, dropping 0.1 to 0.5 mg / mL of a transition metal salt solution, soaking for reaction, filtering, and drying to obtain a precursor material.
7. A method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst according to claim 6, It is characterized in that The concentration of the gel in the solvent is 10 to 50 mg / mL, the mass ratio of the gel to the ruthenium salt is 1:0.01 to 0.2, the concentration of the product in the solvent is 10 to 50 mg / mL, the mass ratio of the ruthenium salt to the transition metal salt is 1:0.1 to 0.3, the temperature of the immersion reaction is 25 to 60°C, and the time is 12 to 24 hours.
8. A method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst according to claim 6, It is characterized in that The ruthenium salt is one or more of hydrated ruthenium chloride, bis(pentamethylcyclopentene)ruthenium, bis(cyclopentene)ruthenium, and (1,5-cyclooctadiene)ruthenium chloride; the transition metal salt is one or more of copper chloride hexahydrate, nickel chloride hexahydrate, cobalt chloride hexahydrate, and manganese chloride tetrahydrate; and the solvent is one or more of deionized water, methanol, ethanol, isopropanol, and ethylene glycol.
9. A method for preparing a bifunctional Schottky heterojunction water electrolysis catalyst according to claim 2, It is characterized in that The sintering treatment is carried out at a temperature of 250-600° C., for a time of 2-8 hours, at a heating rate of 3-5° C. / min, and in an air atmosphere.
10. Use of the bifunctional Schottky heterojunction water electrolysis catalyst according to any one of claims 1 to 9 as an anode or cathode material in hydrogen production by water electrolysis.
Citation Information
Cited By
Biphase heterojunction multi-shell hollow metal oxide electrocatalyst and preparation method thereof
CN120758922A
Preparation method and application of bifunctional heterojunction catalyst for AEM electrolyzed water
CN121593115A
